Repayment capacity, debt service ratios and mortgage default: An exploration in crisis and non-crisis periods - Conor O'Toole; Rachel Slaymaker (The Economic and Social Research Institute (ESRI), 2020)
In this paper, we explore the impact of current household repayment capacity on mortgage default using household-level panel data over the period 2004-2017 for Ireland. We measure repayment capacity as changes in the level of the current debtservice to income ratio to capture a direct channel for affordability shocks. We model the relationship between repayment capacity and default using a discrete time logit survival model of default flows. We test for a non-linear relationship to explore whether negative and positive shocks have asymmetric effects and whether shocks depend on household absorptive capacity. We also test the differing impacts of repayment shocks in crisis and non-crisis times and whether any differences are explained by negative equity or liquidity constraints. A number of endings emerge. We find that deteriorations in current debt service capacity have a positive and increasing effect on default which is dependent on the level of indebtedness or absorptive capacity. We find that the relationship between deteriorations in the repayment capacity and default are worsened in crisis times and we show that this is due to the presence of negative equity and liquidity constraints in these periods.
Keywords: D14; G21; R31; 330; mortgage default; debt-service-ratio; income shocks; loan-to-value ratios